Féminismes et pop culture - Padjemi, Jennifer (Éditions Stock, 2021)
"Dans un essai passionné et engagé, Jennifer Padjemi explore l'alliance, pour le meilleur et pour le pire, des féminismes et de la pop culture. A partir des mouvements féministes modernes, elle décortique le rapport que nous entretenons avec les objets culturels les plus populaires. En utilisant la pop culture comme un miroir de notre société mondialisée, l'auteure interroge les liens d'interdépendance entre consommation de masse et idéologie progressiste, et jette un regard joyeux et lucide sur nos divertissements, sans concession au patriarcat."–Quatrième de couverture.
Section: 283 pages ; 18 cm.
Keywords: afro-féminisme; approches et analyses; care; communication; corps; cours; discipline; féminisme afropéen; féminisme pop; féminismes noirs; intersectionnalité; journalisme; premier cycle; sex2283; sexualité; thématiques; écriture des femmes*; études culturelles

Comment l'impératif écologique aliène les femmes - Bouazzouni, Nora (Slate.fr, 2019)
Qu'elles soient du Sud ou du Nord, les femmes subissent le changement climatique ou les injonctions qui en découlent. C'est à se demander si féminisme et écologie sont compatibles.
Section: Égalités
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; com5170; communication; cours; discipline; environnement; féminisme pop; journalisme; premier cycle; périodes historiques; thématiques; écoféminisme; écologie

The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres